Quantity and location of aortic valve calcification predicts paravalvular leakage after transcatheter aortic valve replacement: a systematic review and meta-analysis - Shi, Jiale; Li, Wei; Zhang, Tangshan; Han, Chengwen; Wang, Zhengjun; Pei, Xinhao; Li, Xuetao; Zhao, Zidong; Wang, Pengbo; Han, Jingying; Chen, Shiqiao (Frontiers in Cardiovascular Medicine, 2023)
Paravalvular leakage (PVL), a serious complication of transcatheter aortic valve replacement (TAVR), is affected by aortic valve calcification. This systematic review and meta-analysis investigated the effect of the location and quantity of calcification in the aortic valve complex (AVC) and left ventricular outflow tract (LVOT) on PVL. Case reports or studies missing detailed data on calcium quantity, containing duplicated datasets, or published in languages other than English were excluded. We used observational studies from PubMed and EMBASE databases from inception until February 16, 2022. Risk of bias was evaluated in Revman, and no significant bias was found. Calcium quantity was expressed as calcium volume or score, detected by multidetector computed tomography (MDCT) using patient-specific detection or fixed threshold. The regions of interest, including the aortic valve leaflets, annulus, and LVOT, were detected similarly using MDCT. PVL assessment was performed using echocardiography after the procedure, at discharge, or after a month. Twenty-four observational studies with 6,846 patients were included in the analysis. A high quantity of calcium was observed in 29.6% of the patients; they showed a higher risk of significant PVL. There was heterogeneity between studies (I2 = 15%). In the subgroup analysis, PVL after TAVR was associated with the quantity of aortic valve calcification, especially those located in the LVOT, valve leaflets, and the device landing zone. A high quantity of calcium was associated with PVL, regardless of valve types or thresholds used. The study is registered in PROSPERO (CRD42022354630).